Femtosecond laser inscribed bragg sensor in terfenol-d coated optical fibre with ablated microslot for the detection of static magnetic fields - Kalli, Kyriacos; Smith, Graham N.; Allsop, Thomas P.; Neal, Ron M.; Sugden, Kate; Culverhouse, Phil F.; Bennion, Ian; Koutsides, Charalambos (My University, 2011)
A novel device for the detection and characterisation of static magnetic fields is presented. It consists of a femtosecond laser inscribed fibre Bragg grating (FBG) that is incorporated into an optical fibre with a femtosecond laser micromachined slot. The symmetry of the fibre is broken by the micro-slot, producing non-uniform strain across the fibre cross section. The sensing region is coated with Terfenol-D making the device sensitive to static magnetic fields, whereas the symmetry breaking results in a vectorial sensor for the detection of magnetic fields as low as 0.046 mT with a resolution of ±0.3mT in transmission and ±0.7mT in reflection. The sensor output is directly wavelength encoded from the FBG filtering, leading to simple demodulation through the monitoring of wavelength shifts that result as the fibre structure changes shape in response to the external magnetic field. The use of a femtosecond laser to both inscribe the FBG and micro-machine the slot in a single stage, prior to coating the device, significantly simplifies the sensor fabrication.
Keywords: Femtosecond lasers; Optical fibers; Fibers